اثر بخشی آموزش یکپارچگی حسی - حرکتی بر کارکردهای اجرایی عزت نفس و روابط با همسالان دانش آموزان با اختلال یادگیری. - سارا محمودی; مریم اکبری (Shenakht Journal of Psychology & Psychiatry, 2025)
Introduction: Learning disorder is one of the most challenging disorders in the field of psychology and special education. Aim: The aim of the present study was to investigate the effectiveness of sensory-motor integration training on executive functions, self-esteem, and peer relationships among the students with learning disabilities. Method: In this study, we used a quasi-experimental design with pre-test and post-test measures, including two experimental groups and a control group. The statistical population comprised all students with learning disabilities who attended the Deep Mind Special Learning Problems Education and Rehabilitation Center in Sanandaj during 2023–2024 academic year. Thirty males with the grades of three to five and learning disabilities were selected through convenience sampling and randomly assigned to two experimental groups (n = 15) and a control group (n = 15). Data were collected using standardized questionnaires assessing executive functions, selfesteem, and peer relationships, alongside a course evaluating the effectiveness of sensory-motor integration. Data analysis was conducted using SPSS version 26 and multivariate analysis of covariance (MANCOVA). Results: The findings showed that sensory-motor integration training is effective in improving executive functions, self-esteem, and peer relationships of students with learning disabilities (P<0.001). The executive function scores increased from 42.5 to 85.6, self-esteem scores increased from 33.25 to 62.43, and peer relationship scores improved from 8.103 to 27.77 following the intervention. Conclusion: The results indicated that the sensory-motor integration intervention, by providing novel experiences, improved executive functions, self-esteem, and peer relationships among students with learning disabilities. These findings suggest that sensory-motor integration can serve as an effective intervention to mitigate challenges faced by this population.